Improving the maintenance program for passenger elevators based on simulation of their operating modes - D. S. Apryshkin; G. Sh. Khazanovich; V. О. Gutarevich (Advanced Engineering Research)
Introduction. Elevators in residential and public buildings are the means of vertical transport. An elevator is one of the complex electromechanical devices of increased danger. Therefore, all stages of its life cycle are strictly limited by regulatory documents. The desired levels of safety and comfort are provided through the reasonable choice of the basic parameters and a constant maintenance of the system in good condition. The key factors that affect the implementation of regulatory requirements during the operation of the elevator installation are the quality of manufacturing of critical components, the level of real workload, taking into account the actual value of the spent resource, and the implemented maintenance program. Currently, when determining the maintenance schedule for elevators, such characteristics as the density of occupancy, the level of power loads, the actual operating time of the elevator and the counts of starts of the main drive are not taken into account. This study objective is the scientific rationale of the concept and methodology for developing the program of maintenance of specific elevator installations on the basis of studies of the level and mode of loading of load-bearing units. Materials and Methods. The use of simulation modeling techniques to assess the load level of power units of an elevator installation and its kinematic indicators under the action of numerous random impacts is validated in the paper. The development of an indicator that characterizes the complex mode of elevator operation, taking into account the joint influence of the level of resource development, net operating time, number of starts, and the power load of the nodes, required the application of an expert method. The final part of the research program is the formation of specific recommendations on the maintenance schedule of elevators. It is based on the ranking of particular indicators. Results. The performance feature of the elevator installation is that the service time of a customer is a function of many random variables. Mathematical models of the formation of force impacts are based on the representation of an electromechanical elevator as a dynamic one-degree-of-freedom system. Expressions for calculating the static tension of traction ropes and torques on the motor shaft are obtained. The problem of dynamics is solved. The loads whose values are the basis for performing simulation modeling of the operating modes of the elevator installation are determined. Discussion and Conclusions. Feasibility of the regulations for the maintenance of passenger elevators is an urgent task, the solution to which determines the level of safety and comfort of passengers. Currently, the standards for the design and operation of elevator installations do not link the frequency of maintenance programs with the level of load and the amount of resource development. The paper provides a general statement of the problem and a methodology for the formation of a complex factor of the equivalent load. Mathematical models are given for calculating the power and temporary loads of the elevator, taking into account the nature of numerous random impacts.